FILING DEVICE - YAMADA HIROSHI; NAKAI YASUTO; YAMADA YUMIKO; NISHIBORI TOSHIKI (1994)
PURPOSE:To quickly and easily register and retrieve materials by performing the filing operation in the same feeling as filing of paper. CONSTITUTION:A tool 40 for filing which has an image of filed sheets of paper 40a as materials and an indicator part 50 which internally displays a cursor 51 indicating the position of the material to be registered or retrieved are laid out on one register and retrieval operation picture 30. A material and page area 60 where the material number and the page number corresponding to the position indicated by the cursor 51 are displayed and a picture display area 70 where a picture 71 included in the material corresponding to the position indicated by the cursor 51 is displayed are laid out in the same picture 30.